THE INVESTIGATION OF THE TEACHING OF WRITING AT THE TENTH GRADE OF SENIOR HIGH SCHOOL (SMAN) 1 AIKMEL IN EAST LOMBOK - ., BASYIRUDIN; ., Prof. Dr. A. A. I. Ngurah Marhaeni,MA; ., Prof. Dr. Nyoman Dantes (Jurnal Pendidikan Bahasa Inggris, 2013)
The study aimed at investigating the quality of the teaching of writing at the tenth grade of Senior High School (SMAN) 1 Aikmel with regard to the implementation of School- Based Curriculum (SBC) in year 2012 / 2013.This research used Context, Input, Process and Product (CIPP) model from Stufflebeam (1986). Context variable is limited only to vision and mission about learning to write, purpose of learning to write and educational policy related to writing. Input is taken as supporting point of the teaching program concerning with teachersÃ¢â¬â¢qualification,s tudentsÃ¢â¬â¢prior knowledge, learning facilities, learning resources , curriculum (SBC) and teacherÃ¢â¬â¢s administration. Process variable includes the teaching and learning process of writing. Product / output is limited to two aspects, namely ; StudentsÃ¢â¬â¢ Writing Competency and StudentsÃ¢â¬â¢ perceiption about the teaching and learning of writing. There were 22 participants used as the subjects of present study , those were 2 English teachers and 20 students of the tenth grade of Senior High School (SMAN) 1 Aikmel . The data were collected using questionaires and observation sheets, then analyzed using quantitative descriptive method. The result showed that ; Context variables were positive , while input, process and product variables were negativekeyword : The Quality of the teaching of Writing , School- Based Curriculum